77.8k views
10 votes
(-2)^-3 x (-3)^-2 Pls help me solve

User Luc VdV
by
5.0k points

1 Answer

8 votes

Answer:


-(1)/(72)

Explanation:

We can solve this by using laws of indices.

To start, laws of indices state:


x^(-y) = (1)/(x^y)

So, let's firstly take the first part of the sum =
-2^(-3)

According to the law shown above:


-2^(-3) = (1)/(-2^3) = (1)/(-8) = -(1)/(8)

Let's now take the second part of the sum =
-3^(-2)

According to the law shown above:


-3^(-2) = (1)/(-3^2) = (1)/(9)

Finally, the sum tells us to multiply those two values together, so we do so:


-(1)/(8) * (1)/(9) = -(1)/(72)

Therefore, our final answer is
-(1)/(72).

User Munez NS
by
5.2k points